Increased stability in self-healing polymer networks based on reversible Michael addition reactions - Kuhl, Natascha; Geitner, Robert; Vitz, Juergen; Bode, Stefan; Schmitt, Michael; Popp, Jürgen; Schubert, Ulrich S.; Hager, Martin D. (Journal of Applied Polymer Science, 2017)
A reversible thiol-ene click reaction is utilized to design novel self-healing polymers. These materials are based on a new methacrylate monomer featuring a benzylcyanoacetamide derivative, which is copolymerized with butyl methacrylate. Afterwards, the crosslinking is performed by the addition of a dithiol and a tetrathiol, respectively. Self-healing behavior is obtained by heating the crosslinked polymers to 100 °C (150 °C) for several hours and is monitored by scratch healing experiments utilizing an optical microscope. The thermal properties are studied in detail by differential scanning calorimetry as well as thermogravimetric analysis. Moreover, depth-sensing indentation measurements are performed to determine the mechanical properties. The healing process is based on the reversible cleavage/closing of the bonds (i.e., thiol-ene reaction), which could be demonstrated by Raman spectroscopy. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 44805.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Michael addition; reversible covalent bonds; self-healing polymers; thiol-ene